Masalah Sosial dan Kebijakan Publik di Indonesia (Studi Kasus UU ITE No. 19 Tahun 2016) - Jayyidan Falakhi Mawaza; Abdussatar Khalil (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2020)
Abstrak This article aims to know and analyze the policy of ITE Law No. 19 of 2016, which has two preferences in the formulation of strategic and political preferences. A good policy comes from social issues that are perceived by many communities and not of individual problems. Public policy is made to resolve social issues not to add or create new problems. Strategic preference in the formulation of this law departs from the problem of many crimes in the form of fraud and evasion by using electronic media. Strategic preference to see this law is passed to address the issue. While political preferences look different about the emergence of this law. The political preference to see the emergence of this law is not separated from the interests of actors who have authority in the making of this law. The actor who has that interest is the ruler. With this law, the ruler is increasingly in limiting and criminalizing the right to freedom of community opinion. This article specifically wants to see the extent of the tension of both preferences.